Efficiency of remote blood pressure monitoring in outpatients with hypertension: a pilot project in a city ambulatory care clinic - Yu. A. Sharapova; I. A. Starodubtseva; S. V. Villevalde (Российский кардиологический журнал)
Aim. In a pilot project, to evaluate the effectiveness of remote blood pressure (BP) monitoring in outpatients followed up for hypertension (HTN).Material and methods. A total of 1,121 patients (707 women and 414 men) with hypertension were included in the pilot project (mean age, 52,0±12,0 years; BP, 151,4±9,1/96,9±10,3 mm Hg). Patients independently measured BP and entered the values into self-management paper diaries (n=886), in digital form to their personal account (n=200), or transmitted data from BP monitor using installed mobile application (n=35). Each of the three groups was assessed at baseline and after 6 months. We assessed achievement of BP targets, medication adherence using the Morisky Green scale, the prevalence of patients with fixed-dose antihypertensive therapy, and the ambulance call rate.Results. Prior to the study, 15,2% (n=171) of hypertensive patients regularly monitored their BP. After 6 months, the mean systolic BP decreased from 151,4±9,1 to 135,5±10,1 mm Hg (p<0,01), diastolic BP — from 96,9±10,3 to 85,8±6,3 mm Hg (p<0,01). The proportion of patients adhering to treatment (Morisky Green score of 4) increased from 17,9 to 55,4%, the frequency of prescribing dual antihypertensive therapy — from 25,8 to 43,3%, triple therapy — from 11,5 to 22,9%, fixed-dose combinations — from 25,4 to 51,6%. At the same time, the proportion of patients who achieved the target BP values increased from 14,5 to 43,1%, while the ambulance call rate decreased from 19,3 to 16,9%.Conclusion. The use of remote BP monitoring methods, including BP monitors with automated data transmission, increases the prescription rate of combined antihypertensive therapy and proportion of patients who achieved the target BP, as well as decreases the ambulance call rate.